2016
DOI: 10.1002/ccd.26621
|View full text |Cite
|
Sign up to set email alerts
|

How to deal with atrial septal defect closure from right internal jugular vein: Role of venous‐arterial circuit for sizing and over‐the‐wire device implantation

Abstract: Secundum atrial septum defect (ASD) is the most common congenital heart disease. It is usually treated by a transcatheter approach using a femoral venous access. In case of bilateral femoral vein occlusion, the internal jugular venous approach for ASD closure is an option, in particular in cases where ASD balloon occlusion test and sizing is needed. Here, we report on a new technique for ASD closure using a venous-arterial circuit from the right internal jugular vein to the femoral artery. Two patients (female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…The right internal jugular vein has also been occasionally used as an alternative venous access site, with good results reported in literature. 3,[6][7][8][9][10] In our patient, in whom the superior caval vein (SCV) was on the left side due to the situs inversus and, in the absence of the inferior caval vein, the manipulation of the devices necessary to implant the prosthesis from the azygos vein or from the right internal jugular through the innominate vein down to the left-sided SVC and the right atrium would be considerably difficult, with great possibility of failure. For this reason, the left internal jugular vein was chosen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The right internal jugular vein has also been occasionally used as an alternative venous access site, with good results reported in literature. 3,[6][7][8][9][10] In our patient, in whom the superior caval vein (SCV) was on the left side due to the situs inversus and, in the absence of the inferior caval vein, the manipulation of the devices necessary to implant the prosthesis from the azygos vein or from the right internal jugular through the innominate vein down to the left-sided SVC and the right atrium would be considerably difficult, with great possibility of failure. For this reason, the left internal jugular vein was chosen.…”
Section: Discussionmentioning
confidence: 99%
“…10 Interestingly, Butera et al reported atrial septal defect cases with bilateral femoral vein occlusion requiring right internal jugular access, in which a venous-arterial circuit with exchange and standard guidewires placed through the defect allowed for adequate balloon sizing and safe overthe-wire device deployment. 7 Another issue that should be considered during the evaluation of alternative access sites for this type of procedure is the possibility of prosthesis embolisation and the difficulties for its retrieval must be anticipated. Dedicated devices for this purpose should be promptly available.…”
Section: Discussionmentioning
confidence: 99%
“…Trans jugular approach using a short manually-curved sheath 4, or a patent ductus arteriosus 180-degree curved sheath instead of the standard ASD 45degree sheath has also been described with many difficulties related to stability during the procedure [4] . This technique was described before in two patients with acquired occlusion of femoral vein [5] , yet this is the first time -to our knowledge -to be reported in a patient with the combination of congenital interruption of the IVC and dextrocardia.…”
Section: Discussionmentioning
confidence: 91%
“…Yet, technical difficulties in transjugular closure of atrial septal defects are well known and frequently encountered. 1,3,4 Several techniques were described to ease the procedure including the "off-label" use of heat-shaped, pre-shaped, or steerable sheath introducers. 1,[3][4][5][6] In transjugular closures, it is certain that a shorter operation path with a shorter delivery system makes device implantation better controlled and less cumbersome.…”
mentioning
confidence: 99%
“…1,3,4 Several techniques were described to ease the procedure including the "off-label" use of heat-shaped, pre-shaped, or steerable sheath introducers. 1,[3][4][5][6] In transjugular closures, it is certain that a shorter operation path with a shorter delivery system makes device implantation better controlled and less cumbersome. Therefore, the off-label use of intermediate-length sheaths is an ideal alternative.…”
mentioning
confidence: 99%